Preferensi Konsumen Terhadap Keputusan Pembelian D.co Pizza Bondowoso Sebagai Produk Alternatif - Yulianti, Riska; Saleh, Mohammad; Jumiati, Aisah (IJABAH, 2025)
Currently there is widespread news regarding calls for action to switch to alternative products from companies that support Israel's genocide against Palestine, one of which is through an international boycott under the command of Boycott, Divestment, Sanctions. One of the BDS lists is another quite controversial boycott list, including Pizza Hut, MCD, Wix, Burger King, Papa John's Pizza and Domino's Pizza. The Indonesian Ulema Council also issued MUI Fatwa number 83 of 2023 as a response to the Palestinian struggle. The above phenomenon makes people more careful in buying products that are on the boycott list and start switching to alternative products, namely local products. One of the local Bondowoso products which is an alternative product is D.Co Pizza Bondowoso which has its own competitiveness and characteristics. separately, but it is not yet known exactly what factors influence people's shift to alternative products, especially at D.Co Pizza Bondowoso. This research aims to determine and analyze the influence of knowledge of MUI fatwa number 83 of 2023 and religiosity on purchasing decisions for D.Co Pizza Bondowoso. The method used is explanatory research using binary logistic regression analysis. From the results of logistic regression analysis calculations, a significant relationship was obtained between knowledge on purchasing decisions and religiosity on purchasing decisions.